Advances in Ferroptosis Research: A Comprehensive Review of Mechanism Exploration, Drug Development, and Disease Treatment - Haojie Wang; Yuanyuan Xie (Pharmaceuticals)
In recent years, ferroptosis, as an emerging modality of programmed cell death, has captured significant attention within the scientific community. This comprehensive review meticulously canvasses the pertinent literature of the past few years, spanning multiple facets. It delves into the intricate mechanisms underpinning ferroptosis, tracks the evolution of its inducers and inhibitors, and dissects its roles in a diverse array of diseases, as well as the resultant therapeutic implications. A profound exploration is conducted of the functional mechanisms of ferroptosis-related molecules, intracellular pathways, metabolic cascades, and signaling transduction routes. Novel ferroptosis inducers and inhibitors are introduced in detail, covering their design blueprints, synthetic methodologies, and bioactivity profiles. Moreover, an exhaustive account is provided regarding the involvement of ferroptosis in malignancies, neurodegenerative disorders, cardiovascular ailments, and other pathologies. By highlighting the pivotal status and potential therapeutic regimens of ferroptosis in various diseases, this review aspires to furnish a thorough and profound reference framework for future investigations and clinical translations in the ferroptosis domain.